Marrying a Righteous Woman as the Preferred Choice: An Analysis of Hadith Sanad and Matan - Bona Bargot Riezky Nagabe Siregar; Insan Akbar (AJIS: Academic Journal of Islamic Studies, 2024)
Marriage represents an essential stage in a Muslim’s life, undertaken after finding a suitable partner and achieving mental and financial readiness. This study explores the criteria for selecting a pious woman (woman ṣāliḥah) through an analysis of sanad and matan. The main objective is to identify and examine these criteria using perspectives from Hadith studies, sociology, and psychology. Theoretically, this research proposes a new conceptual framework that integrates traditional Hadith analysis with modern social and psychological insights. Academically, the findings are expected to enrich the field of Hadith Studies by offering new perspectives on how sanad and matan contribute to understanding women’s piety in the context of marriage. Practically, the study provides valuable guidance for society, especially for men seeking to build stable and harmonious marriages based on Islamic principles. The research employs a qualitative or library-based approach, analyzing textual sources and scholarly opinions. The study finds that the criteria for marrying a pious woman can be evaluated not only through religious authenticity but also from sociological and psychological standpoints. The original contribution of this work lies in its relevance to modern Muslim men, helping them identify key traits of a ṣāliḥah woman as a preferred choice in marriage. The findings suggest that marrying someone of the same faith and similar background enhances harmony and marital satisfaction. Homogamous marriages—those between individuals sharing values, beliefs, and lifestyles—tend to be more enduring and successful. In this context, ṣāliḥah refers to a woman with deep religious understanding and moral integrity.